Total Pancreatectomy and Islet Auto-Transplantation as Treatment for Ampullary Adenocarcinoma in the Setting of Pancreatic Ductal Disruption Secondary to Acute Necrotizing Pancreatitis. A Case Report - Iyegha, Uroghupatei P; Asghar, Javariah A; Beilman, Greg J (JOP. Journal of the Pancreas, 2012)
Context Ampullary adenocarcinoma is the third most common periampullary malignancy. Obstruction of the main pancreatic duct is linked with an increased incidence of acute pancreatitis. Acute necrotizing pancreatitis leading to pancreatic duct disruption carries significant morbidity. When these conditions occur in combination, the treatment can be drastically limited as pancreaticoduodenectomy is not a viable option in the setting of friable ductal tissue, which precludes pancreatic ductal anastomosis and can lead to the complications of leak or stricture. Case report Our patient is a 72-year-old woman who developed pancreatic ductal disruption and splenic vein thrombosis as a result of acute necrotizing pancreatitis. Concurrently, she was found to have an ampullary adenoma with high-grade dysplasia. Her treatment options were limited, as she was neither a candidate for pancreaticoduodenectomy given the ductal disruption nor total pancreatectomy, which would render her a brittle diabetic. She was successfully treated with total pancreatectomy and islet auto-transplantation thereby resecting her ampullary lesion while both avoiding a pancreatic anastomosis and preserving pancreatic endocrine beta-cell function. Conclusion We report a case where total pancreatectomy and islet auto-transplantation can be considered as a viable option for treatment of ampullary lesions in a setting where standard surgical options are suboptimal.